16 Air Assault Brigade the history of Britain's Rapid Reaction Force - Ripley, Tim (Pen & Sword Aviation, 2008)
After the S.A.S., 16 Brigade is the most high profile formation in the British Army but to date there has been no complete history of its operations and activities. The aim of this book is to produce a history of Britain's Elite Rapid Reaction Force 16 Air Assault Brigade. It covers military hardware, the Brigade has some of the UK's most advanced weapon system, including Apache attack helicopters. It includes the elite combat units including the Parachute Regiment and Pathfinders.